2014
DOI: 10.1016/j.cell.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Macrophage Enhancer Landscapes Are Shaped by the Local Microenvironment

Abstract: SUMMARY Macrophages are critical for innate immune defense and also control organ homeostasis in a tissue-specific manner. They provide a fitting model to study the impact of ontogeny and microenvironment on chromatin state and whether chromatin modifications contribute to macrophage identity. Here, we profile the dynamics of four histone modifications across seven tissue-resident macrophage populations. We identify 12,743 macrophage-specific enhancers and establish that tissue-resident macrophages have distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

96
1,829
4
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,774 publications
(1,992 citation statements)
references
References 64 publications
96
1,829
4
9
Order By: Relevance
“…Moreover, ATMs failed to show clustering with macrophages from liver, lung, brain, peritoneum or intestines (Extended Data. 3e), consistent with specialized function of ATMs 16 . Furthermore, co-expression analysis identified 1,887 highly connected genes with age, which were visualized as a network (Extended Data 4a, b).…”
Section: Main Textsupporting
confidence: 70%
“…Moreover, ATMs failed to show clustering with macrophages from liver, lung, brain, peritoneum or intestines (Extended Data. 3e), consistent with specialized function of ATMs 16 . Furthermore, co-expression analysis identified 1,887 highly connected genes with age, which were visualized as a network (Extended Data 4a, b).…”
Section: Main Textsupporting
confidence: 70%
“…Moreover, another study compiled a comprehensive catalog of enhancer histone marks at the single‐cell level, and unveiled that there exists significant de novo establishment of lineage‐specific enhancers during hematopoiesis 25. Similarly, based on single‐cell profiling of histone modifications dynamics in different tissue‐resident macrophages populations, the same group showed that a combination of tissue‐ and lineage‐specific transcription factors form the regulatory networks controlling chromatin specification in tissue‐resident macrophages 26.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
“…This field has been propelled by remarkable technological advances for efficiently isolating single cells 28, 29, and the reduction of the detection levels of protocols for profiling gene expression 30, 31, histone marks 25, 26, or chromatin accessibility 32, 33 in individual cells. These techniques allow researchers to overcome the limitations of population studies, in which averaging the measurements over a heterogeneous population of cells masks the variability at the epigenetics and transcriptional levels among cells within a culture or tissue 26, 34, 35. Moreover, the analysis of large numbers of single cells provides statistical power for predicting functional correlations among genes 36 in different cells within a heterogeneous population, hence facilitating the reconstruction of subpopulation‐specific gene regulatory networks that determine priming for commitment to different cell fates.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
See 2 more Smart Citations